The Role of Social Media and Digital Technology in Increasing Psychological Vulnerability in Adolescents - Mabanja, Ashiraf; Puspitasari, Intan (Advances in Psychological Sciences and Applications, 2025)
The widespread use of digital technologies has reshaped adolescent socialization and learning while raising concerns about mental health vulnerability. This review synthesizes ten empirical studies (2017–2024) examining links between digital technology use and adolescent psychological outcomes. Six studies reported positive associations between technology use and negative outcomes such as depression, anxiety, and suicidal ideation, while two identified dose–response patterns showing greater risk with heavier or problematic use. Longitudinal findings indicated temporal precedence, where increased technology use preceded declines in well-being. Gender emerged as a consistent moderator, with adolescent girls experiencing stronger negative effects, and pre-existing mental health conditions further amplifying risk. Although some adolescents reported benefits like social connection and online support, the overall evidence suggests that excessive or emotionally driven technology use heightens psychological vulnerability. Preventive strategies should emphasize digital literacy, emotional regulation, and gender-sensitive approaches. Future research should employ longitudinal and objective methods to clarify causal mechanisms linking digital engagement and adolescent well-being.